2006
DOI: 10.1016/j.neuroimage.2005.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Cytology and functionally correlated circuits of human posterior cingulate areas

Abstract: Human posterior cingulate cortex (PCC) and retrosplenial cortex (RSC) form the posterior cingulate gyrus, however, monkey connection and human imaging studies suggest that PCC area 23 is not uniform and atlases mislocate RSC. We histologically assessed these regions in 6 postmortem cases, plotted a flat map, and characterized differences in dorsal (d) and ventral (v) area 23. Subsequently, functional connectivity of histologically guided regions of interest (ROI) were assessed in 163 [ 18 F] fluorodeoxyglucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
360
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(399 citation statements)
references
References 77 publications
33
360
1
1
Order By: Relevance
“…Instead, PCC activity was negatively associated with individual differences in parasympathetic activity in the context of grief elicitation. Although unexpected, this is an exciting new result, as recent projection studies have demonstrated specific connectivity between the PCC and the sACC (Vogt et al, 2006), which projects to the autonomic nuclei in the brainstem (Neafsey et al, 1993).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Instead, PCC activity was negatively associated with individual differences in parasympathetic activity in the context of grief elicitation. Although unexpected, this is an exciting new result, as recent projection studies have demonstrated specific connectivity between the PCC and the sACC (Vogt et al, 2006), which projects to the autonomic nuclei in the brainstem (Neafsey et al, 1993).…”
Section: Discussionmentioning
confidence: 88%
“…Recent projection maps have shown that there are functional differences between the dorsal PCC (dPCC) and the ventral PCC (vPCC; Vogt et al, 2006). Vogt and colleagues propose a division between dPCC, which orients the body in space via the cingulate motor areas, and the vPCC, which interacts with sACC to process self-relevant emotional and nonemotional information and objects.…”
Section: Discussionmentioning
confidence: 99%
“…2A). In view of the highly heterogeneous nature of the PCC (26,36), the fact that some regions play a generic role in memory, whereas a subregion in the RSC is selective for semantic word fluency, is not surprising. Similarly, interregional connectivity analyses yielded distinguished connectivity patterns during the two mnemonic conditions: elevated coactivation between the precuneus and ventral anterior cingulate during the semantic condition and between the precuneus and the left IPL during the episodic condition (Fig.…”
Section: Contributions Of Dmn Subcomponents To Specific Aspects Of Mementioning
confidence: 99%
“…The CC is implicated in a diverse array of functions, such as emotion (George et al., 1995; Kross, Davidson, Weber, & Ochsner, 2009; Liotti et al., 2000; Rogers et al., 2004; Rolls, Grabenhorst, & Parris, 2008; Walter et al., 2008, 2009), movement (Beckmann, Johansen‐Berg, & Rushworth, 2009; Paus, 2001; Picard & Strick, 1996, 2001), self‐relevant assessment (Kelley et al., 2002; Vogt, Vogt, & Laureys, 2006), cognition (Luo et al., 2007; Pourtois et al., 2010; Sohn, Albert, Jung, Carter, & Anderson, 2007; Ursu, Clark, Aizenstein, Stenger, & Carter, 2009), memory (Maguire, 2001), visuospatial orientation (Vogt et al., 2006), navigation, imagination, and planning for the future (Vann, Aggleton, & Maguire, 2009). …”
Section: Introductionmentioning
confidence: 99%